Cook-off test and numerical simulation of AP/HTPB composite solid propellant. (March 2016) - Yang, Hou-Wen; Yu, Yong-Gang; Ye, Rui; Xue, Xiao-Chun; Li, Wen-Feng
Abstract: A small-scale cook-off experimental apparatus is designed to study the thermal security problem of ammonium perchlorate/hydroxyl-terminated polybutadiene (AP/HTPB) propellant. Both fast and slow cook-off tests are carried out. Then a cook-off model is established according to the apparatus, and compared with the experimental results. The theoretical calculation results are in good agreement with the experimental data. On this basis, the numerical predictions of cook-off properties of a solid rocket motor are performed at different heat fluxes. Results show that the initial cook-off response locations of AP/HTPB propellants all occur in the annular region on the outer wall of the propellant near the nozzle under the three kinds of heating flux conditions. The insulating effect of the insulating layer in the motor increases as the heat flux is increasing. When the heat flux is 10 3 W m −2, 10 4 W m −2 and 10 5 W m −2, the ignition delay time is 5071.5s, 348.5s and 41.0s, with the corresponding ignition temperature of 533.89 K, 554.97 K and 590.07 K, and the shell temperature of 521.38 K, 597.08 K and 837.92 K during the ignition near the nozzle. It can be concluded that the ignition delay time of the propellant is significantly shortened, and the ignition temperature as well as the shell temperature during the ignition near the nozzle increases gradually when the heat flux is increasing. Graphical abstract: A small-scale experimental apparatus is designed to study the cook-off characteristics of AP/HTPB propellant. Then a cook-off model is established according to the apparatus, and compared with the experimental results. The theoretical calculation results are in good agreement with the experimental data. On this basis, the numerical predictions of cook-off properties of a solid rocket motor are performed at different heat fluxes. Highlights: Both fast and slow cook-off tests are conducted with an experimental apparatus. A cook-off model of AP/HTPB propellant is established according to the experimental conditions. The numerical simulations of cook-off properties of a solid rocket motor are performed at different heat fluxes.